(3fXe GdeYdheGJ GdGSJQGJjLjI (B:s (3efXhQ GdejRI GdGSJQGJjLjI (B/s - (3GdWGFj, eMeO YHO MSjfs; (3GdNaGLj, fYeI YHGS NVjQ s ((3YeGf(B: s (3OGQ GdKbGaI(B, s, 2009)
(3eaghe fXe GdeYdheGJ GdESJQGJjLjI heHQQGJ XghQgG(B- (3GdeYdheGJ GdESJQGJjLjI hNUGFUgG(B- (3aGYdjI fXe GdeYdheGJ GdESJQGJjLjI(B- (3GdJNWjW dJUeje fXe GdeYdheGJ GdESJQGJjLjI(B- (3OhQ fXe GdeYdheGJ GdESJQGJjLjI aj HfGA GdejRI GdJfGaSjI(B- (3GdJWHjbGJ GdESJQGJjLjI dfXe GdeYdheGJ GdESJQGJjLjI(B- (3feGPL fXe GdeYdheGJ GdESJQGJjLjI heJWdHGJ JWHjbgG aj GdOhd GdfGejI(B.s
(3eQGLY U(B.299 (3; edMb GdeUWdMGJ U(B.287s
Keywords: (3EOGQI GdGYeGds; (3GdGOGQIs; (3GdeYdheGJs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s